2017
DOI: 10.3390/ijms18102095
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics Mediate Microbial Interactions in a Consortium of the Infant Gut Microbiome

Abstract: Abstract:Composition of the gut microbiome is influenced by diet. Milk or formula oligosaccharides act as prebiotics, bioactives that promote the growth of beneficial gut microbes. The influence of prebiotics on microbial interactions is not well understood. Here we investigated the transformation of prebiotics by a consortium of four representative species of the infant gut microbiome, and how their interactions changed with dietary substrates. First, we optimized a culture medium resembling certain infant gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…The lack of a consistent body of data indicating significant impacts of an administered probiotic on the microbiota (Chua et al, ; Kankainen et al, ; Kristensen et al, ; Medina, Pinto, Ovalle, Thomson, & Garrido, ) should not be taken as indicative of a lack of biological effects. Indeed, effects of an orally administered probiotic on the systemic immune system (Groeger et al, ; Konieczna, Akdis, Quigley, Shanahan, & O'Mahony, ) and on brain responses (Pinto‐Sanchez et al, ; Wang, Braun, Murphy, & Enck, ) have, indeed, been demonstrated in human studies.…”
Section: Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a consistent body of data indicating significant impacts of an administered probiotic on the microbiota (Chua et al, ; Kankainen et al, ; Kristensen et al, ; Medina, Pinto, Ovalle, Thomson, & Garrido, ) should not be taken as indicative of a lack of biological effects. Indeed, effects of an orally administered probiotic on the systemic immune system (Groeger et al, ; Konieczna, Akdis, Quigley, Shanahan, & O'Mahony, ) and on brain responses (Pinto‐Sanchez et al, ; Wang, Braun, Murphy, & Enck, ) have, indeed, been demonstrated in human studies.…”
Section: Probioticsmentioning
confidence: 99%
“…The lack of a consistent body of data indicating significant impacts of an administered probiotic on the microbiota (Chua et al, 2017;Kankainen et al, 2009;Kristensen et al, 2016;Medina, Pinto, Ovalle, Thomson, & Garrido, 2017) should not be taken as indicative F I G U R E 2 Interactions between the microbiota, dietary components and host. (a) Health.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Location correlations can suggest the type of symbiosis between members of the microbiota, including whether these are mutualistic or competitive (Geva‐Zatorsky et al ., ). Visualization of colony clustering on its own can be strong evidence for the cooperation or exclusion of microbes (Geva‐Zatorsky et al ., ), but further assays to assess the negative or positive response of one species to another can help solidify understanding of these relationships (Portal‐Celhay and Blaser, ; Medina et al ., ) by determining how these characteristic microbiota are established and how they avoid colonization by foreign bacteria (Wong et al ., ; Kwong et al ., ). Changes in these correlations can be indicative of community health or disturbance.…”
Section: Identifying Microbiota–microbiota Interactionsmentioning
confidence: 99%
“…Microbiota preferentially digest dietary prebiotics, including fiber, which are not easily digestible by the host. In individuals consuming low-fiber diets, insufficient supply of prebiotics may prompt changes in microbiome composition and metabolism that affects host metabolism [158]. While this process is complex, and confounded by many variables influencing body weight and food choice, subtle differences in energy availability over time could be enough to shift individuals from a lean to an obesogenic phenotype [159,160].…”
Section: Mechanisms Linking Altered Microbiome Composition To Devementioning
confidence: 99%